EXTRACTABLE ALUMINIUM RELATIONSHIPS TO SOME SOIL PROPERTIES IN SUB-HUMID FOREST ZONE OF SOUTHERN NIGERIA - ISIRIMAH , N. O.; LOGANATHAN, P. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Thirty-four surface soil samples (0-15cm), twenty-four from the Coastal Plain Sands (CPS) and ten from the Meander Belt Delta Soils (MBD) were collected from two geophysiographical different areas in the Rivers State of Southern Nigeria. The relationship of extractable Aluminium with some soil properties (i. e. % clay, % silt, % organic matter and pH) are considered. The KC1 extractable Al of Coastal Plain sand (CPS) soils largely Ultisols were significantly correlated with all soil properties while the NH4OAc pH 4.8 extractable Al, in some CPS soils were not significantly correlated with any of the soil properties. However, the Meander Belt Delta (MBD) soils largely ENTISOLS & INCEPTISOLS with higher pH, Al extracted by both KC1 and NH4OAc showed striking relationship to soil properties. Two soil samples (one CPS - Ultisols and the other MBD Entisols) were amended by addition of cattedung or poultry or piggery manure and/-or with lime (CaCO3) material and incubated at 50% moisture level for six weeks, and were processed, for determination of KCI and NH4OAc extractable Aluminium. Results obtained showed that poultry and/or piggery manure were more effective amendment materials for the management of pH and active Aluminium pool in the soils considered. More future indepth work using various organic manure/ wastes with lime mixtures is suggested.